2004
DOI: 10.1177/0013161x04267118
|View full text |Cite
|
Sign up to set email alerts
|

Formal Mentoring Programs in Education and Other Professions: A Review of the Literature

Abstract: The sheer volume of literature on mentoring across a variety of disciplines is an indication of the high profile it has been afforded in recent years. This article draws on a structured analysis of more than 300 research-based articles on mentoring across three discipline areas in an attempt to make more valid inferences about the nature and outcomes of mentoring. It begins by reporting on the findings compiled from a database of research articles from educational contexts. These research-based articles are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
355
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(406 citation statements)
references
References 29 publications
(50 reference statements)
10
355
0
16
Order By: Relevance
“…In their review of mentoring within the fields of education, business, and medicine, Ehrich et al (2004) found that "professional expertise and / or personality mismatch" was one of two most frequently cited problems with mentoring relationships. For mentees, this problem was mentioned in 12.6% of studies and for mentors 17%.…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 99%
“…In their review of mentoring within the fields of education, business, and medicine, Ehrich et al (2004) found that "professional expertise and / or personality mismatch" was one of two most frequently cited problems with mentoring relationships. For mentees, this problem was mentioned in 12.6% of studies and for mentors 17%.…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 99%
“…Given such mentoring benefits have been identified, it is reasonable that higher education institutions, including universities and specifically engineering schools, invest resources to introduce mentoring programmes where they do not exist or increase the effectiveness of existing ones. However, in spite of the benefits, one key challenge of the mentoring field is the lack of a unified and generally accepted conceptualisation of mentoring (Jacobi, 1991;Crisp & Cruz, 2009;Gershenfeld, 2014;Ehrich et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we apply the developed framework to the study of the more than fifty years of mentoring engineering students at a Spanish University, a non-English speaking context (hereinafter referred to as the engineering university). As most of the mentoring research to date has been carried out in the US and other English speaking countries Ehrich et al, 2004;Kezar & Kinzie, 2006), this descriptive study of a mentoring experience is one of the first in a Spanish cultural context. Subsequently, the usefulness of the framework with the case studied will be verified and areas for improving the effectiveness of the mentoring programme at the engineering university will be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The topic attracts a plethora of literature that is reviewed on a regular basis (Jacobi 1991;Ehrich, Hansford, and Tennent 2004;Terrion and Leonard 2007;Crisp and Cruz 2009). Peer mentoring involves more experienced students supporting new students during their academic and personal development, and has been found to be effective in: improving the first-year experience of students (see, for example, Watson 2000;Hensen 2003;Mee-Lee and Bush 2003;Farrell et al 2004;Tariq 2005); increasing student retention (see, for example, Packham and Miller 2000;Boud, Cohen, and Sampson 2003;Muldoon 2008); improving achievement, with some suggesting peer mentoring users gain higher mean grades than non-users (see, for example, Congos, Langsham, and Schoeps 1998;Ashwin 2002;2003); and improving the interpersonal skills of the mentors, which leads to enhanced employability (see, for example, Congos and Stout 2003;McLean 2004;Muldoon 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The key success factors consistently identified include appropriate mentor training and the inclusion of peer mentoring as part of the formal curriculum (Jacobi 1991;Ehrich Hansford, and Tennent. 2004;Terrion and Leonard 2007;Crisp and Cruz 2009).…”
Section: Introductionmentioning
confidence: 99%